2016
DOI: 10.1111/ajt.13655
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Perfusate Biomarkers and Pump Parameters With Delayed Graft Function and Deceased Donor Kidney Allograft Function

Abstract: Hypothermic machine perfusion (HMP) is increasingly used in deceased-donor kidney transplantation, but controversy exists regarding the value of perfusion biomarkers and pump parameters for assessing organ quality. We prospectively determined associations between perfusate biomarkers [neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), interleukin-18 (IL-18) and liver-type fatty acid-binding protein (L-FABP)] and pump parameters (resistance and flow) with outcomes of delayed gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 35 publications
4
87
1
1
Order By: Relevance
“…Consequently, kidneys from NHBDs should not be discarded because of high concentration of a perfusate biomarker. Similar conclusions were reached by Parikh et al (57) in the largest prospective multicenter cohort study, which investigated associations among perfusate biomarkers (NGAL, KIM-1, IL-18, L-FABP ) and pump parameters (resistance and flow) with DGF and allograft eGFR at six months. Recently Guy et al (58) effectuated one-dimensional proton-nuclear magnetic resonance spectroscopy on 45-min and 4-h perfusate samples from 26 kidneys to demonstrate that 28 different metabolites varied in concentration during HMP, while specific metabolites (leucine, inosine, gluconate, and glucose) predicted DGF.…”
Section: Perfusate Biomarkerssupporting
confidence: 80%
“…Consequently, kidneys from NHBDs should not be discarded because of high concentration of a perfusate biomarker. Similar conclusions were reached by Parikh et al (57) in the largest prospective multicenter cohort study, which investigated associations among perfusate biomarkers (NGAL, KIM-1, IL-18, L-FABP ) and pump parameters (resistance and flow) with DGF and allograft eGFR at six months. Recently Guy et al (58) effectuated one-dimensional proton-nuclear magnetic resonance spectroscopy on 45-min and 4-h perfusate samples from 26 kidneys to demonstrate that 28 different metabolites varied in concentration during HMP, while specific metabolites (leucine, inosine, gluconate, and glucose) predicted DGF.…”
Section: Perfusate Biomarkerssupporting
confidence: 80%
“…In spite of the poor predictivity of the selected perfusate biomarkers for short‐term graft outcomes, perfusate NGAL and L‐FABP measured near the end of machine perfusion as well as pump parameters (resistance and flow) were modestly associated with six‐month eGFR. Although the study found lacking or weak prognostic utility of the most known biomarkers of ischemia‐reperfusion injury in the perfusate, additional candidate molecules involved in other pathways might deserve further research, especially in view of the growing organ shortage and the critical issue relative to kidney allocation acceptance or refusal decisions 55.…”
Section: Ngal As a Perfusion Marker In Kidney Preserved By Hypothermimentioning
confidence: 91%
“…NGAL has been also evaluated as a hypothermic machine perfusion biomarker for assessing organ quality in deceased donor kidney transplantation 53, 54, 55.…”
Section: Ngal As a Perfusion Marker In Kidney Preserved By Hypothermimentioning
confidence: 99%
“…Recently, Parikh et al demonstrated an association between DGF and several markers in cold machine-perfused donor kidney perfusates, including KIM-1, IL-18, and liver fatty acid binding protein (L-FABP) (29), none of which associated with DGF in our discovery panel. Similarly, YKL-40 (in serum and urine) could be detected, but showed no association with DGF.…”
Section: Discussionmentioning
confidence: 65%
“…Urinary NGAL has been demonstrated to predict DGF with reasonable accuracy (AUC approximately 0.8) (27), and also plasma and serum NGAL levels at day 1 after transplantation are higher in recipients that develop DGF (16,17,28). An association between DGF and NGAL levels in donor kidney perfusate has been described for machine-perfused kidneys (29).…”
Section: Discussionmentioning
confidence: 95%